Indonesia's rise & its regional implications - Emirza Adi Syailendra (2013)
Indonesia's projected rise as a medium power may see at least two likely scenarios. The first is one of power diffusion while the second sees Indonesia asserting a greater leadership role in the Asia Pacific. What are the implicatios for the region?